Cracking Facebook The Importance of Understanding Technology-Based Communication - Leena Korpijaakko, Maria (Youth, Media, and Culture Series, 2015)
This book presents a Facebook study on members of the Cusp Generation, or those born before the "great digital divide" of 1995. This delineation allows for a discussion on the possible socio-cultural implications of Facebook use for people of all ages. Members of the Cusp Generation are in a unique position as "part digital natives" to easily acquire and use new media technologies, while being more critically aware of the personal, social, and cultural effects that may arise from them thanks to having some memory of the pre-digital era. Readership: Educational Researchers and their students